Expression and Function of VEGFRs in Normal Epidermis and Psoriatic Lesional Keratinocytes: VEGFRs in normal epidermis and psoriatic lesional keratinocytes - Wang, Yong; Yan, Yong; Yu, Huiwen; Jiang, Guangrong; Zhao, Shiying; Yi, Meng (Cellular and Molecular Biology, 2023)
The study aimed to explore the expression and function of VEGFRs in normal epidermis and keratinocytes of psoriatic lesions. In this study, the expression and role of VEGFRs in keratinocytes were examined using examples from psoriatic and healthy individuals. The experiment was completed by immunofluorescence analysis, reverse transcription polymerase chain reaction, Western blot, and real-time quantitative RT-PCR after the skin of nonlesional, adjacent, and lesional skin was excised. Observations indicated that in non-lesional psoriatic areas and adjacent lesional areas of the skin of psoriasis patients, the fluorescent signals of VEGFR-1 and VEGFR-2 were strongly labelled with keratinocytes, and in psoriatic lesions, keratinocytes were present throughout the entire thickness of the epidermis, with the exception of the stratum corneum. The distribution of VEGFR-3 in psoriatic nonlesional and adjacent lesional skin was consistent with that in normal epidermis, whereas all layers of the epidermis of psoriatic lesions expressed VEGFR-3. The mRNA expression levels of VEGFR-1,2,3 steadily increased from the normal epidermis to the psoriatic nonlesional, adjacent lesional, and perilesional areas, with the lesional epidermis' keratinocytes exhibiting the greatest levels of mRNA expression. Ca ions upregulate VEGFR-1,2,3 mRNA and protein expression in keratinocytes of nonlesional areas of psoriasis. VEGFRs protein expression and cortical IOD values of psoriatic and normal population cells showed a positive correlation. Hence, in comparison to normal epidermal keratinocytes, psoriatic lesional regions' keratinocytes considerably enhanced their expression of VEGFR-1,2,3 mRNA and protein. The overexpression of VEGFR-1,2,3 in psoriatic lesions may be encouraged by VEGF and Ca þ ions.